1979
DOI: 10.1161/01.cir.59.4.632
|View full text |Cite
|
Sign up to set email alerts
|

Carotid baroreflex function in young men with borderline blood pressure elevation.

Abstract: Volunteers, ages 19-25 years, were recruited from 900 university students whose blood pressures were measured during registration. Blood pressures of each volunteer were measured two to four (average 2.85) times with subjects in the sitting position, after 10 minutes of rest. Weight, height and skin fold thickness, measured in the midline midway between the chin and the upper margin of the thyroid cartilage were also measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 20 publications
4
37
0
Order By: Relevance
“…When the arterial system is less compliant, this results in a continuous increased stretch of the baroreceptors, causing a downregulation, i.e., a loss of sensitivity, in turn altering autonomic function by lowering parasympathetic modulation and increasing sympathetic outflow. Support for this attenuation in BRS has been observed in normotensive relatives of hypertensive patients (18,59). Furthermore, the loss of BRS has been shown to be a major risk factor for cardiovascular morbidity and mortality in postmyocardial infarction patients (34,53).…”
Section: Discussionmentioning
confidence: 87%
“…When the arterial system is less compliant, this results in a continuous increased stretch of the baroreceptors, causing a downregulation, i.e., a loss of sensitivity, in turn altering autonomic function by lowering parasympathetic modulation and increasing sympathetic outflow. Support for this attenuation in BRS has been observed in normotensive relatives of hypertensive patients (18,59). Furthermore, the loss of BRS has been shown to be a major risk factor for cardiovascular morbidity and mortality in postmyocardial infarction patients (34,53).…”
Section: Discussionmentioning
confidence: 87%
“…It has been demonstrated that there is marked reduction of baroreflex control of heart rate in essential (Bristow et al, 1979;Korner et al, 1974) and borderline (Eckberg, 1979;Takeshita et al, 1975) hypertension in humans. This finding has been taken to indicate a generalized impairment of the arterial baroreflexes, including baroreflex control of the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…ment of arterial baroreflex control of heart rate in hypertension (Bristow et al, 1969;Eckberg, 1979;Korner et al, 1975;Takeshita et al, 1975), it has been suggested that there may be a generalized impairment of baroreflex control of the peripheral circulation. We recently reported (Guo et al, 1982) that, in normotensive animals, baroreflex control of heart rate may be impaired when baroreflex control of hindlimb resistance is preserved.…”
Section: This Manuscript From the University Of Iowa Was Sent To Fohnmentioning
confidence: 99%
“…4 -10 Cardiac, but especially skeletal muscle, sympathetic outflow are strongly modulated by baroreflexes, and some authors suggest that the increase of sympathetic neural activity could be the result of an early impaired inhibitory influence of arterial baroreceptors. [11][12][13] However, the increased peripheral sympathetic discharge does not seem to be localized to tissues under baroreflex control, because we have recently demonstrated in prehypertensive and hypertensive SHR that an increased release and metabolism of NE is also detectable in the subcutaneous adipose tissue, 14 -15 where sympathetic activity is relatively independent from the baroreflex function. 16,17,18 In contrast to skeletal muscle sympathetic activity, the impulses to subcutaneous adipose tissue show no signs of pulse-synchronous grouping and no correlation with spontaneous fluctuations of blood pressure, suggesting that baroreflex modulation is weak or absent, depending mainly on metabolic and thermoregulatory influences.…”
mentioning
confidence: 94%